Medical Professional Liability Risk among U.S. Cardiologists - Mangalmurti, Sandeep (2014)
BACKGROUND: MPL remains a significant burden for physicians, in general, and cardiologists, in particular, as recent research has shown that average MPL defense costs are higher in cardiology than other specialties. Knowledge of the clinical characteristics and outcomes of lawsuits against cardiologists may improve quality of care and risk management. METHODS: We analyzed closed MPL claims of 40,916 physicians and 781 cardiologists insured by a large nationwide insurer for at least one policy year between 1991 and 2005. RESULTS: The annual percentage of cardiologists facing a MPL claim was 8.6%, compared to 7.4% among physicians overall (p<0.01). Among 530 claims, 72 (13.6%) resulted in an indemnity payment, with a median size of $164,988. Mean defense costs for claims resulting in payment were $83,593 (s.d. $72,901). The time required to close MPL claims was longer for claims with indemnity payment than claims without (29.6 vs 18.9 months, p < 0.001). More than half of all claims involved a patient’s death (304; 57.4%), were based on inpatient care (379; 71.5%), or a involved a primary cardiovascular condition (416; 78.4%). Acute coronary syndrome was the most frequent condition (234; 44.2%). MPL claims involving non-cardiovascular conditions were common (66, 12.5%) and included falls or mechanical injuries suffered while under a cardiologist’s care and a failure to diagnose cancer. CONCLUSIONS: Rates of malpractice lawsuits are higher among cardiologists than physicians overall. A substantial portion of claims are non-cardiovascular in nature.